2018
DOI: 10.31306/s.60.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety trends in construction, mining and transportation sectors in Turkey

Abstract: SUMMARY: Production processes in construction, mining and transportation involves high risks of occupational accidents all over the world. In 2014, 25.6% of the total accidents and 65% of fatal accidents occured in these three sectors in Turkey. According to the Eurostat data, in 2014, 20% of all work-related accidents and 38% of fatal accidents have occurred in these sectors in EU. The fatality rates in Turkey are very high compared to EU countries. In Turkey, these sectors have high accident risks due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Numerous organisations use diverse approaches, such as implementing management systems subject to evaluation and certification, to evaluate and improve their risk management strategies for their products, services, and operations. Several The topic of workplace accidents is a multifaceted occurrence that encompasses a range of factors capable of impacting diverse outcomes, such as health, job satisfaction, and absenteeism (Amponsah- Yilmaz & Tosun, 2018). The existing body of empirical research conducted over the past thirty years has consistently identified two essential components contributing to workplace accidents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous organisations use diverse approaches, such as implementing management systems subject to evaluation and certification, to evaluate and improve their risk management strategies for their products, services, and operations. Several The topic of workplace accidents is a multifaceted occurrence that encompasses a range of factors capable of impacting diverse outcomes, such as health, job satisfaction, and absenteeism (Amponsah- Yilmaz & Tosun, 2018). The existing body of empirical research conducted over the past thirty years has consistently identified two essential components contributing to workplace accidents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multi-causal accident models consider the influence of diverse, complex interdependent factors. Thus, an accident-influencing factor need not necessarily directly cause damage but may be indirectly associated with the accident, such as organizational or cultural aspects (Eskandari et al, 2017;Muchiri et al, 2019;Sawhney & Cigularov, 2018;Thurston & Glendon, 2018;Yilmaz & Tosun, 2018;Gembalska-kwiecień, 2017;Keffane, 2015;Motter & Santos, 2017;Rashid et al, 2014;Šarotar Žižek & Mulej, 2016;Zwetsloot et al, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, the technical and social components of the work environment were considered in this study. The role of personal predispositions and the influences exerted on them by these technical and social systems were examined (Gembalska-kwiecień, 2017;Jackson et al, 2012;Sakina & Omar, 2018;Sheikhalishahi et al, 2017;Yilmaz & Tosun, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Production equipment used in many mines (and some construction sites) is often outdated, defective or has been neglected (Nowrouzi-Kia et al, 2017). As a consequence, many fatal occupational accidents occur due to the machines and hand tools used in the exploitation (Yilmaz & Tosun, 2018) The main objective of this research is to find evidence of the mining equipment resulting in occupational accidents and what are the conditions more prone to accidents.…”
Section: Introductionmentioning
confidence: 99%